Figli di una «creatività minore»? Che cosa pensano le persone normodotate del connubio creatività-disabilità - Fabio Bocci; Gianmarco Bonavolontà; Walter Nanni (LED Edizioni Universitarie, 2013)
Children of a «Lesser Creativity »? What Able-bodied People Think about the Correlation between Creativity and Disability. The authors of this article illustrate the results of an exploratory survey conducted with a group of 567 people, with different internal and external roles in the educational context. The aim of the research is to detect the most common beliefs about human creativity, in particular the relationship between creativity and disability. In spite of multiple and heterogeneous definitions, human creativity is generally conceived as a gift enjoyed only by a few people, whereas people with disabilities are said to represent the weak link of such a conception. According to data analysis, the approaches to the conception of creativity can be grouped into four macro types: a «Selective» type, a «Universalist» type, a «Utopian» type, a «Genetically fatalist» type. The authors have identified and codified these types on the basis of the position of the sample with respect to four possible intersections resulting from the correlation between the belief that creativity is either innate or acquired and the belief that creativity is either a universal factor or a «gift» for a few people. As to the creativitydisability relation, the data, linked with the above macro types, have pointed out diversified attitudes between «groups», thus confirming their internal validity. However, within the types considering creativity a universal factor, a lack of homogeneity can sometimes be detected, as a result of dissimilar socio-cultural views and attitudes that still exist.